Management of the Qur'an Education Park Institution in Improving Al-Qur'an Education - Rama Dinan Krishnan; Nurdyansyah Nurdyansyah (Indonesian Journal of Islamic Studies, 2022)
This study aims to reveal and analyze how the management of TPQ institutions in improving al-Qur'an education in TPQ Ar Rahmah wal Barokah Surabaya. This type of research uses qualitative research with a descriptive approach. Data collection techniques using the method of observation, interviews, and documentation. Then the data obtained in the field, analyzed through three stages, namely: (1) the data reduction stage, (2) the data presentation stage, (3) the conclusion drawing stage. The results of the research on the management of the TPQ institution in improving al-Qur'an education at TPQ Ar Rahmah wal Barokah can be said to be good, this can be seen from (1) the analysis of the management indicators of the TPQ Ar Rahmah wal Barokah institution that has been managed which consists of a) elements agency management includes: 1) man (HR); 2) money (funds); 3) machines (machines); 4) methods (method); 5) materials (sarpras); 6) market (marketing); b) the management functions of a well-managed TPQ institution consist of: 1) Planning; 2) organizing; 3) implementation; 4) supervision. Meanwhile, the obstacles to the management of TPQ institutions in improving Qur'anic education at TPQ Ar Rahmah wal Barokah Surabaya are, among others: (a) The organizing function has not been fully implemented; (b) The passing standard of students can only be measured by the munaqis of the institution, namely the head and internal of the institution. Keywords: Management, TPQ Institute, Al-Qur'an Education